(untitled) (Research, Society and Development, 2022)
The growing period of tilapia (Oreochromis niloticus) for the industrialization of fillets in fish processing plants is around 8 to 9 months. The production and industrialization in a shorter time, adding value to the product, can be a market alternative. With the focus on proposing the canning of this species, this work aimed to analyze the fish body yield, microbiological quality of undersized tilapia below commercial slaughter standard for fillet production. A total of 100 tilapia were used, in a 2x3 factorial experiment, consisting of 2 treatments (in natura and canned packaging), each with 3 levels (large (259.90 to 373.33 g); medium (118.30 to 256.51g) and Small (48.51 to 112.56 g). After dissection, the samples were packed in plastic bags marked with their respective size categories and then frozen for subsequent canning. Statistical analysis was performed to determine whether there was an effect of weight on the characteristics of the fish in natura and to determine the effect of size and packaging on chemical composition. The set of characteristics of weights, morphometric measurements and yields were analyzed using the Kruskal-Wallis test and comparisons between levels of the factors analyzed using the unpaired Wilcoxon test. Size classes differed statistically (P<0.05) for the weight, length and yield variable. The yield results obtained showed an increasing trend as a function of size with average values of 45.07% ± 2.60% for the small size, 46.49% ± 1.43% for the medium size, and 49.43% ± 2.31% for the large size. The values found for the chemical composition of the clean log demonstrate that there was an effect of the size (P<0.05) of the fish in relation to the ash content, with the size characterized as large having higher ash content in relation to the others. Finally, the canned and in natura products presented body and microbiological yields that make the production and its industrialization feasible.